PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PERKULIAHAN PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS SRIWIJAYA - Ali Bardadi; Mgs Afriyan Firdaus; Firdaus - (Jurnal Sistem Informasi, 2010)
One of the information system used by higher education management information system lecture. Sriwijaya University Faculty of Computer Science is the faculty who already have management information systems classes, but in that system, there are still shortcomings and therefore systems must be developed in order to improve the quality of higher education. The method used in this study is the method of system development FAST (Framework for the Application of Systems Techniques). Â  Kata kunci : Sistem Informasi Manajemen Perkuliahan, Fakultas Ilmu Komputer Universitas Sriwijaya, FAST (Framework for the Application of Systems Techniques)